Change in willingness to COVID‐19 vaccination in China: Two online surveys during the pandemic. Issue 11 (23rd July 2022) - Huang, Ninghua; Wang, Chao; Han, Bingfeng; Zhao, Tianshuo; Liu, Bei; Chen, Linyi; Xie, Mingzhu; Zheng, Hui; Zhang, Sihui; Wang, Yu; Juan, Du; Liu, YaQiong; et al.
Abstract: Objective: As the variants of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) continue to emerge, periodic vaccine booster immunization may become a normal policy. This study investigated the changes and factors associated with vaccination intentions in various epidemic situations, which can provide suggestions for the construction and modification of routine vaccination program strategies. Methods: Two cross‐sectional online surveys were conducted in January and June of 2021. The willingness and confidence of the coronavirus disease 2019 (COVID‐19) vaccination were measured following propensity score matching (PSM) treatment. The difference in the willingness for COVID‐19 Vaccination in the two surveys was analyzed by single or multi‐factor analyses. Results: The willingness to accept the SARS‐CoV‐2 vaccine was higher in the second survey than that in the first survey (90.5% vs. 66.6%, p  < 0.001). Concerns about the vaccine's safety declined (71.0% vs. 47.6%, p  < 0.001), but concerns about the efficacy increased (22.4% vs. 30.9%, p  < 0.001). Confidence in the SARS‐CoV‐2 vaccine had an important impact on the increased uptake willingness (odds ratio = 3.19, 95% confidence interval: 2.23–4.58, p  < 0.001). Conclusions: There has been a significant increase in attitudes towards the SARS‐CoV‐2 vaccine which was associated with higher vaccine confidence. Vaccine effectiveness received more concerns from respondents rather than safety after nearly 6 months' utilization of the SARS‐CoV‐2 vaccine. It indicates that aggressive communication and timely disclosure of vaccine data can build vaccine confidence.